Employee Communication Analysis at PT Telkom Sumedang - Firyal Rohadatul Aisy; Aa Kartiwa; M. Irfan Nur'arif (Journal of Bussines Management Basic, 2022)
In this study, the focus of research is Employee Work Communication at PT Telkom Kandatel Sumedang. The purpose of this study is to find out how work communication is at Telkom Sumedang and to find out how to improve employee work communication at Telkom Sumedang. The research method used is a qualitative research method, using a sampling technique in the form of purposive sampling. Data collection techniques were carried out by interview, observation, documentation and triangulation. To obtain information, the researchers determined three informants, including the head or head of Telkom Sumedang, sales promotions and technicians. Based on the results of this study that employee work communication at PT Telkom Sumedang is optimal but not evenly distributed. It can be seen from the readiness and alertness of each employee in carrying out their duties. Efforts to overcome so that communication is evcenly distributed, leaders must communicate more directly (face to face) with employees personally, motivate and evaluate employee performance. With the habit of communicating directly with the leadership, employees will be optimal in carrying out their work and improve the quality of communication to provide written and oral messages. Employees must also be more thorough and follow the applicable procedures.